If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + -36 = -72 Reorder the terms: -36 + -4x = -72 Solving -36 + -4x = -72 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '36' to each side of the equation. -36 + 36 + -4x = -72 + 36 Combine like terms: -36 + 36 = 0 0 + -4x = -72 + 36 -4x = -72 + 36 Combine like terms: -72 + 36 = -36 -4x = -36 Divide each side by '-4'. x = 9 Simplifying x = 9
| -16+m=-20 | | 5=9+4x | | 0.5(4x+8)(x)=20 | | 4c=16.8 | | -19=x-17 | | 6y-(2y-5y)=29 | | 1.48(k+3)=5.92 | | b+14=1 | | d+(-7)=12 | | 6x+3=98-3x+6 | | 7+1-6x+3x=3x-5x | | q+6.44=0.72 | | k+18=32 | | -p+7=13 | | 5(-2v+6)-4v=-2(v-3) | | 7.2=1.8x | | -2*-0.36=x | | -20=a-8 | | 7.1=x-1.4 | | -2.65(g-10)=-15.9 | | 2a^2-6a+13=0 | | v-19=-36 | | 17.6=3.9(p+3)+2 | | -8h=-48 | | 15m+4+9m=-32 | | 5(3x-9)-2=5(x-3)+28 | | -8=-5+n | | w+175=98 | | 9x-(3x-7)=25 | | 13-16g+4g=25 | | 46=2(12)+2(b) | | a-7=-26 |